Thermo-Economic Analysis of Combined Cycle MED-TVC Desalination System. (August 2015) - Hanafi, A.S.; Mostafa, G.M.; Fathy, A.; Waheed, A.
Abstract: In the present work, thermo-economic model of a superstructure combined cogeneration power plant is studied. Engineering Equation Solver "EES" code is used to study the enhancement of the thermal performance, the environmental impact and the economics cost of the plant. Optimum design point for maximum production of power and water is obtained, through developing mathematical model of separate system, and combined cogeneration system, at different operating conditions. Also, economics model, including capital cost of each unit, fuel cost, operating and maintenance cost, is developed. It is concluded that, the combined cogeneration system can save about 20.6% of Total Annual Cost "TAC" compared with separate power and water production system. The cogeneration plant consists of Gas Turbine (GT), Heat Recovery Steam Generator (HRSG), Steam Turbine (ST) and Multi Effect -Thermo Vapor Compressor Desalination System (MED-TVC).